Detonation Velocity Measurement with Chirped Fiber Bragg Grating - Peng Wei; Hao Lang; Taolin Liu; Dong Xia (Sensors, 2017)
Detonation velocity is an important parameter for explosive, and it is crucial for many fields such as dynamic chemistry burn models, detonation propagation prediction, explosive performance estimation, and so on. Dual-channel detonation velocity measurement method and system are described. The CFBG sensors are pasted both on the surface and in the center of the explosive cylinder. The length of CFBG sensors is measured via the hot-tip probe method. The light intensity reflected from the CFBG sensors attached to the explosive is transformed to voltage, and the voltage–time is then measured with the oscilloscope. According to the five experiments results, the relative standard uncertainty of detonation velocity is below 1%.